Effect of a Training Program on Emergency Nurse's Knowledge and Skills in Triage (Journal of Hama University, 2019)
Triage aims to improve the quality of emergency care and priority. The Triage in the emergency department refers to determining the time of care for each patient or allocating of the necessary resources to the patient by looking for immediate ways to provide care for patients in critical condition and to post-pone care to patient In the less severe case. Decision-making in this case is a complex process. Several triage system measures have been designed to guide the screening nurse to the right decision, which supports decision-making. The triage criteria are based on vital signs of patients (respiratory rate, oxygen saturation, The level of awareness and temperature of the body) and the main complaint of the patient. This research includes a semi-experimental study through the implementation of a training program based on the Australian triage Scales (ATS) on the nursing staff in emergency departments at Al Assad University Hospital and the National Hospital in Lattakia , and assess the level of information and skills of emergency nurses before starting the application of the training program and after its application and compares it with other studies .The results of the study shows an improvement in the level of information and skills of emergency nurses in the application of the process of screening patients after undergoing the training program in terms of significance compared to the nurses Who are left to Daily - hospital